Is the polarization of the CC bond imperative for bifunctional outer-sphere CC hydrogenation?. Issue 5 (6th February 2023) - Ai, Xinliang; Xie, Xiaofeng; Song, Xueqing; Li, Longfei; Schaefer III, Henry F.
Abstract : The DFT study suggests that the polarization of CC bonds is not the controlling factor of outer-sphere bifunctional CC bond hydrogenations. Instead, the "push–pull" type π-conjugative effect can contribute to these reactions. Abstract : Understanding controlling factors is important for the development of bifunctional outer-sphere CC hydrogenations. A dominant view is that the polarization of CC bonds is imperative for these reactions. However, the present comparative DFT study suggests that the polarization of CC bonds is not the controlling factor. Instead, the "push–pull" type π-conjugative effect can decrease activation barriers and contribute to outer-sphere bifunctional CC bond hydrogenations. What is more, this study shows the feasibility of the asymmetric bifunctional outer-sphere CC hydrogenation.